Effect of Zeolite Addition on Urea Fertilization Efficiency in Mustard Greens (Beassica juncea L.) - Diatna, Elin; Muspiah, Aida; Farista, Baiq (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Leaching of nitrogen nutrients in urea fertilizer application is a common problem in vegetable cultivation, including mustard greens (Brassica juncea L.). To address this problem, zeolite is added to the urea fertilizer to maximize the nutrient absorption by plants. This study aims to determine the effect of zeolite addition at various urea fertilizer concentrations on the growth of mustard greens and its effect on the efficiency rate of nutrient adsorption. This research is conducted on March up to May 2023 by using a completely randomized design (CRD) with 8 treatments, namely P0 (control, without urea and without zeolite), P1 (2 gr urea + 200 gr zeolite), P2 (4 gr urea + 200 gr zeolite), P3 (6 gr urea + 200 gr zeolite), P4 (8 gr urea + 200 gr zeolite), P5 (2 gr urea), P6 (4 gr urea), P7 (6 gr urea), and P8 (8 gr urea). Each treatment was repeated three times and put inside a greenhouse. The results showed that the combination of urea and the addition of zeolite to the planting medium gave higher values ​​on leaf area, number of leaves, wet weight and dry weight of mustard plants compared to the treatment of urea fertilizer without zeolite and also the control. The P4 treatment gave the largest leaf area (81.61 cm2) and the largest number of leaves (10.33). The P4 treatment also showed the highest results in wet weight and dry weight, namely 115 grams of wet weight and 9.3 grams of dry weight. The absorption efficiency was higher in the combination treatment of urea fertilizer and the addition of zeolite compared to the treatment of urea fertilizer and without zeolite or with the control. Meanwhile, the highest efficiency was found in the P4 treatment at 56.45%. This finding indicates that the addition of zeolite into the fertilizer can promote the growth of the mustard green.